How adolescents understand their values: A qualitative study. (January 2021) - Lewis-Smith, Iona; Pass, Laura; Reynolds, Shirley
An important component of some psychological therapies is the use of clients' values to motivate behaviour change. Values are understood to be developed during childhood and adolescence but there has been limited exploration of how young people experience values and their function across contexts. This study aimed to explore adolescents' understanding of the concept of 'values' and to elicit their experiences of values. Semi-structured, individual interviews were conducted with 11 adolescents aged 12–17 years. Thematic analysis was used to identify themes. Young people were readily able to discuss the meaning of 'values' and their own personal values. Three main themes were identified: (1) what values are (in general, and specific to themselves), (2) where values come from (relationships, education, growing up), and (3) why values are important (prioritising/decision making, reflecting on values is helpful). The adolescents in this study demonstrated an in-depth understanding of the meaning, origins and functions of values. The results suggest young people may welcome and benefit from opportunities to discuss their values, including in therapy.